Diagnostic Value of Risk Nomogram for the Prediction of Postpartum Hemorrhage Following Vaginal Delivery - Nazpari Ashouri; Masoumeh Kordi; Mohammad taghi Shakeri; Fatemeh Tara (Mashhad University of Medical Sciences, 2019)
Background: Postpartum hemorrhage (PPH) is considered as one of the major causes of maternal mortality worldwide. The most effective risk factors have been suggested in various studies on risk nomogram for the prediction of PPH. Aim: This study aimed to determine the diagnostic value of the risk nomogram for the prediction of PPH. Method: This study was performed prospectively using diagnostic methods on 600 women admitted to Omolbanin Hospital, Mashhad, Iran, from May to October 2017. The researcher measured and recorded the loss of blood volume in mothers using plastic blood collection bags and pads within 4 h after delivery. Subsequently, risk nomogram was completed for each study sample and the probability score for PPH was calculated by the researcher's assistants. The obtained data were analyzed in SPSS software (Version 25). Ultimately, the receiver operating characteristic (ROC) curve of risk nomogram was plotted in this study. Results: The PPH occurred in 33.3% (n=200) of deliveries in this study. The area under the ROC curve was estimated at 81.2%. The point of 0.1 with 85.5% sensitivity and 51.5% specificity was also selected as the proposed cut-off point for this nomogram. Implications for practice: According to the results, the risk nomogram was considered as an appropriate method for the prediction of PPH. Therefore, it was recommended as a simple and noninvasive approach in childbirth for the prediction of PPH.